Sistem Informasi Banten Otonan di Era Society 5.0 - Warmayana, I Gede Agus Krisna (Institut Hindu Dharma Denpasar, 2020)
Banten means for the Hindu people to prostrate themselves to devotion to God Almighty. In this study, the researchers wanted to preserve the special offerings that are digital-based in this era of society 5.0, in which this era has a lot of digital/computerized and automatic technology used by the community. In this era, the community will at least be affected by the pattern and order of life. Autonomy is birth based on wuku and sapta ware. The development of the otonan began to be forgotten, with birthdays based on the birth date. Judging from this guideline, the researcher wants to build a strategy for preserving Banten Otonan and building a digital information system based on a survey of internet and social media usage for more than 50% of Indonesia's population who use it. Therefore the researchers made strategies on social media to provide information on offerings, and a website information system was built as a forum for information to find out the offerings and how to implement them.